2014
DOI: 10.4236/aim.2014.43021
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic and Growth Promoting Effects of <i>Lactobacillus plantarum</i> AK Isolated from a Nigerian Fermented Cereal Product on Rats Fed High Fat Diet

Abstract: The hypocholesterolemic effect of Lactobacillus plantarum AK strain was tested in rats fed high cholesterol diet. The lipid profile, growth rate and microflora dynamics of rats that received L. plantarum AK strain were significantly different from the control group (p < 0.5). In particular low density lipoprotein was lower in serum of rats that received L. plantarum than those of the control group. The test group had a higher growth rate, higher lactobacilli counts but lower coliform and Escherichia coli count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…The microbial population in the cecum provides evidence for cecal fermentation (Liyanage et al, ). Although there was no difference in Bifidobacteria and Lactobacilli populations among experimental groups, lower cecal coliform population in mung bean diet‐fed rats compared to the control group indicated that mung bean diets may have improved the cecal microbial balance in rats as suggested previously (Akanbi & Agarry, ).…”
Section: Resultssupporting
confidence: 65%
“…The microbial population in the cecum provides evidence for cecal fermentation (Liyanage et al, ). Although there was no difference in Bifidobacteria and Lactobacilli populations among experimental groups, lower cecal coliform population in mung bean diet‐fed rats compared to the control group indicated that mung bean diets may have improved the cecal microbial balance in rats as suggested previously (Akanbi & Agarry, ).…”
Section: Resultssupporting
confidence: 65%
“…The main function of serum LDL is to transport the cholesterol synthesized by the liver to the tissue, and the main function of serum HDL is to transport the excess cholesterol from the tissue back to the liver for degradation [ 33 ]. In this study, compared with that of the control, the serum LDL content of weaned piglets treated with FBSPW did not change significantly, and the serum HDL content increased, especially in the piglets treated with 8% FBSPW, corroborating the results of Akanbi and Agarry [ 34 ]. These results indicate that the addition of FBSPW to the feed of weaned piglets improved the protein and lipid metabolisms of piglets, and this may be related to the prebiotics contained in the FBSPW because prebiotics can improve the protein and lipid metabolism functions of pigs [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 90%
“…21 The presence of Lactobacillus in sufficient amounts is associated with decreasing cholesterol levels in serum in experimental animals. 22 Studies using in vitro, cell culture, and in vivo animals indicated probiotics can bind and prevent the absorption of aflatoxins, which have been demonstrated to be implicated in the etiology of liver cancer in humans, 23,24 a rat model of ethanol-induced liver damage, which has been used to demonstrate the protective effects of probiotics. 25 A recent review supported the use of probiotics in at least those patients with an end-stage kidney disease.…”
Section: Introductionmentioning
confidence: 99%